Adsorption and wettability study of methyl ester sulphonate on precipitated asphaltene - Okafor, H.; Sukirman, Y.; Gholami, Raoof (2016)
Asphaltene precipitation from crude oil and its subsequent aggregation forms solid, which preferentially deposit on rock surfaces causing formation damage and wettability changes leading to loss of crude oil production. To resolve this problem, asphaltene inhibitor has been injected into the formation to prevent the precipitation of asphaltene. Asphaltene inhibitors that are usually employed are generally toxic and non-biodegradable. This paper presents a new environmentally friendly asphaltene inhibitor (methyl ester sulphonate), an anionic surfactant, which has excellent sorption on formation rock surfaces. Result from adsorption study validated by Langmuir and Freundlich models indicate a favourable adsorption. At low volumes injected, methyl ester sulphonate is capable of reverting oil-wet sandstone surface to water-wet surface. Biodegradability test profile shows that for concentrations of 100-5000ppm it is biodegradable by 65-80%.